Assessment of progesterone levels on the day of pregnancy test determination: A novel concept toward individualized luteal phase support - Racca, A.; Alvarez, M.; Garcia Martinez, S.; Rodriguez, I.; Gonzalez-Foruria, I.; Polyzos, NP.; Coroleu, B. (Frontiers in Endocrinology, 2023)
Research question: The main objective of the study is to define the optimal trade-off P4 values on the day of ET, to identify low P4-hCG, and to establish whether P4 supplementation started on the hCG-day can increase the success rate of the FET-cycle. Design: A single-centre, cohort, retrospective-study with 664 HRT-FET cycles analysed where all women received vaginal P4 600mg/day starting from 6 days before the FET, had normal P4 values on the day- before-ET and were inspected for P4 on the day of pregnancy test. Results: Of the 664 cycles, 69.6% cycles showed P4≥10.6 ng/ml, while 30.4% showed P4<10.6 ng/ml on the day of the hCG. Of the 411 chemical pregnancies detected 71.8% had P4-hCG≥10.6ng/mL (group-A), while 28.2% had P4-hCG<10.6ng/mL. 64.7% (group-B) cycles with P4-hCG <10.6ng/mL were supplemented with a higher dose of vaginal P4 (1000 mg/day), while 35.3% (group-C) were kept with the same dose of vaginal micronized P4. Live birth rate was respectively 71.9%, 96% and 7.3 % for group A, B and C. Conclusion: The likelihood to detect P4-hCG<10.6 ng/mL decrease as the level of serum P4 the day before ET increases. LBR showed to be significantly lower where P4 was low and not supplemented.